2011
DOI: 10.1080/03079457.2011.592822
|View full text |Cite
|
Sign up to set email alerts
|

Multi-locus sequence typing and plasmid profile characterization of avian pathogenicEscherichia coliassociated with increased mortality in free-range layer flocks

Abstract: Avian pathogenic Escherichia coli strains originating from 10 free-range layer flocks were characterized by multi-locus sequence typing and plasmid profile analysis to investigate their phylogenetic relationship and diversity, respectively. In addition to colibacillosis, all flocks tested positive for antibodies against avian metapneumovirus (aMPV) during production, and six of the flocks were concurrently affected by histomonosis. Accumulated average mortality for flocks concurrently affected by colibacillosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
6
11
0
Order By: Relevance
“…E. coli infections are often considered opportunistic whenever the bacteria of concern display great genetic variation. Limited genetic diversity of E. coli bacteria has been reported associated with acute haemorrhagic septicaemia in turkeys (Olsen et al, 2011a), in E. coli septicaemia lesions following cellulitis in chickens (Jeffrey et al, 2002) and in EPS cases found in free-range layer flocks (Olsen et al, 2011b). Also in the present study, limited genetic variation amongst E. coli colonies from bone marrow of laying hens with EPS was found.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…E. coli infections are often considered opportunistic whenever the bacteria of concern display great genetic variation. Limited genetic diversity of E. coli bacteria has been reported associated with acute haemorrhagic septicaemia in turkeys (Olsen et al, 2011a), in E. coli septicaemia lesions following cellulitis in chickens (Jeffrey et al, 2002) and in EPS cases found in free-range layer flocks (Olsen et al, 2011b). Also in the present study, limited genetic variation amongst E. coli colonies from bone marrow of laying hens with EPS was found.…”
Section: Discussionsupporting
confidence: 45%
“…However, four PFGE types shared ST 95. In the present study, 12 STs were detected, while Olsen et al (2011b) found eight STs in 10 flocks of free-range layers with EPS. Both studies revealed five STs in common (ST 23,ST 57,ST 95,ST 117 and ST 141).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…All strains isolated from wild pigeon and parrot were pathogenic, while there were both pathogenic and nonpathogenic strains isolated from chickens (MLST database). The ST117 (SEPT362 -septicemic) is frequently found in APEC strains, in fact, this ST was the most prevalent type detected in two different studies that determined ST for E. coli isolates from several Danish broiler breeders and layer farms (Gregersen et al 2010, Olsen et al 2011) and in the MLST database. This ST is also associated to human urinary tract infections (UTI) (Wu et al 2012).…”
Section: Resultsmentioning
confidence: 99%